Further investigation of the effect of upstream solar-wind fluctuations on solar-wind/magnetosphere coupling: Is the effect real? - Borovsky, Joseph E. (Frontiers in Astronomy and Space Sciences, 2023)
There is a general consensus that fluctuations in the solar wind magnetic field and/or the Alfvenicity of the solar wind drive a solar wind-magnetosphere interaction. 11 years of hourly-averaged solar wind and magnetospheric geomagnetic indices are used to further examine this hypothesis in detail, confirming that geomagnetic activity statistically increases with the amplitude of upstream fluctuations and with the Alfvénicity, even when solar-wind reconnection driver functions are weak and reconnection on the dayside magnetopause should vanish. A comparison finds that the fluctuation-amplitude effect appears to b stronger than the Alfvénicity effect. In contradiction to the generally accepted hypothesis of driving an interaction, it is also demonstrated that many solar wind parameters are correlated with the fluctuation amplitude and the Alfvénicity. As a result, we caution against immediately concluding that the latter two parameters physically drive the overall solar-wind/magnetosphere interaction: the fluctuation amplitude and Alfvénicity could be acting as proxies for other more-relevant variables. More decisive studies are needed, perhaps focusing on the roles of ubiquitous solar-wind strong current sheets and velocity shears, which drive the measured amplitudes and Alfvénicities of the upstream solar-wind fluctuations.